PRODUCTIVITY THROUGH SOIL CONSERVATION PROGRAMMES- A CASE OF MAYURAKSHI RIVER VALLEY PROJECT - kumar, N. Prem (Journal of Soil and Water Conservation, 2022)
In Mayurakshi catchment a case study of 10 mini watershed has been carried out to determine multiple benefits specially productivity through soil conservation including afforestation works. Lack of forest cover ( only over 6% of total area) and confining biotic domage, to a great entint overshadesved the positive effects of other soil conservation works: Assessment offuel, fodder and other bomass needs of the house holds should be made and activition to increase their production awed to slopped up significantly. There should be grassroot level management of resources developed The other increases like golly pinge, water harvesting etc. should cacontiuce to be the infegred of the watershed management programme.